2015
DOI: 10.1007/s11934-015-0558-y
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Experience with Partial Nephrectomy for Stage T2 or Greater Renal Tumors

Abstract: The purpose of this paper is to review current studies on the topic of partial nephrectomy (PN) for renal masses stage T2 and greater. We conducted a PubMed literature review of English language articles published from 2000 onward. Eight studies were selected for this review including 359 PN patients. Median tumor size was 7.5 to 8.7, and tumor histology was mainly clear cell. Technique was mainly open, the reported median ischemia time was 29-45 min, and median operative time 170-221 min. Positive margin rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Retrospective studies reported patients with cT2a tumors demonstrated less differences in eGFR at 12 months than patients with with cT1 tumors after open, LPN and RPN. 13,29 Before our study, however, no studies have compared reduction in eGFR after one postoperative year between TRPN and RRPN in patients with ‡4 cm renal tumors. In our study, change in eGFR at 1 year postoperation was significantly more decreased at 1 year after RRPN than after TRPN for all patients ( p = 0.006) and patients with ‡4 cm renal tumors ( p = 0.008).In patients with ‡4 cm renal tumors, mean decrease in eGFR at 1 year postoperation was more than 10% for RRPN.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies reported patients with cT2a tumors demonstrated less differences in eGFR at 12 months than patients with with cT1 tumors after open, LPN and RPN. 13,29 Before our study, however, no studies have compared reduction in eGFR after one postoperative year between TRPN and RRPN in patients with ‡4 cm renal tumors. In our study, change in eGFR at 1 year postoperation was significantly more decreased at 1 year after RRPN than after TRPN for all patients ( p = 0.006) and patients with ‡4 cm renal tumors ( p = 0.008).In patients with ‡4 cm renal tumors, mean decrease in eGFR at 1 year postoperation was more than 10% for RRPN.…”
Section: Discussionmentioning
confidence: 99%
“…But overall, we demonstrated a significant OS benefit after NSS ( Fig 1 ). Very few studies addressed elective NSS for pT2 or higher rated renal tumors [ 12 , 14 , 24 28 ]. Jelders et al included only 29 NSS patients, as Breau et al included only very few patients undergoing elective NSS in their cohorts, both groups did not provide any information about the imperative indication of NSS [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multi‐study review of both open and laparoscopic PNs showed minimal change in chronic renal function compared with baseline . At discharge, renal function was inferior in the T2a group undergoing PN, however this difference equilibrated at 12‐month follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to PN being increasingly performed for larger tumours . A few studies have shown that open and laparoscopic PN for T2a tumours is safe, with low peri‐operative complication rates ; however, there are only a few case reports on the feasibility of RAPN for T2a tumours . Radical nephrectomy (RN) is still used for many cT1b tumours and is the recommended treatment for T2a (7 to <10 cm) and greater tumours .…”
Section: Introductionmentioning
confidence: 99%